PERAN TOKOH AGAMA DALAM PENANGGULANGAN PERGAULAN BEBAS BAGI REMAJA (SUATU STUDI DI DESA DOLODUO KECAMATAN DUMOGA BARAT) - Bonde, Andika; Kandowangko, Nicolas; Zakarias, John (HOLISTIK, Journal Of Social and Culture, 2019)
The younger generation is the backbone of the nation, which is expected in the future is able to pass on the baton of the relay of the struggle and the leadership of the nation in order to be better. Globalization has been going decline in morals, morals and decency, their impact is certainly related to problems towards them into free association. As the younger generation should think more clear avoid norms or decency layout deemed to deviate from the neighborhood association. Deviant behavior impacts as a result of free association may give rise to excesses or the social impact that also affect their behavior from drift norms, norms, morality or law that among other things consuming liquor, drugs/addictive substances, free Sex, gambling and so on. The issue of free association can be affected by the problem of the lack of social control especially of the elderly, the problem of uncontrolled environments as well as the existence of the Era of globalization. The influence of strong drink among teenagers enough potentially to the problems of crime in particular sexual crimes, crimes through fights between free-range. In order to reduce the problem of free association, then it takes the role of religious figures. Because religion is one of the alternatives in reducing and tackling the existence of free intercourse among teenagers. In addition the role of families is very important in shaping the personality of the adolescent, because from a parent or keluargalah fortress personal resilience of teenagers can be formed. Keywords: youngers, generation, globalization